Biofuels : Markets, Targets and Impacts - Timilsina, Govinda R.; Shrestha, Ashish (2012)
This paper reviews recent developments in biofuel markets and their economic, social and environmental impacts. Several countries have introduced mandates and targets for biofuel expansion. Production, international trade and investment have increased sharply in the past few years. However, several existing studies have blamed biofuels as one of the key factors behind the 2007-2008 global food crisis, although the magnitudes of impacts in these studies vary widely depending on the underlying assumptions and structure of the models. Existing studies also have huge disparities in the magnitude of long-term impacts of biofuels on food prices and supply; studies that model only the agricultural sector show higher impacts, whereas studies that model the entire economy show relatively lower impacts. In terms of climate change mitigation impacts, there exists a consensus that current biofuels lead to greenhouse gas mitigation only when greenhouse gas emissions related to land-use change are not counted. If conversion of carbon rich forest land to crop land is not avoided, the resulting greenhouse gas release would mean that biofuels would not reduce cumulative greenhouse gas emissions until several years had passed. Overall, results from most of the existing literature do not favor diversion of food for large-scale production of biofuels, although regulated production of biofuels in countries with surplus land and a strong biofuel industry are not ruled out. Developments in second generation biofuels offer some hope, yet they still compete with food supply through land use and are currently constrained by a number of technical and economic barriers.